Jews and health tradition, history, and practice - Hezser, Catherine 1960- (Leiden Boston Brill, 2023)
"The contributions in Jews and Health: Tradition, History, Practice examine the significance of the preservation of physical, mental, and spiritual health in the Jewish tradition and in Jewish societies from ancient to modern times from multiple thematic and methodological perspectives. The authors -- Carmen Caballero Navas, Maria Diemling, William Friedman, Catherine Hezser, Magdaléna Jánošíková, Reuven Kiperwasser, Katherine E. Southwood, Irit Offer Stark, and Nimrod Zinger -- deal with definitions and representations of health in biblical, Jewish Hellenistic, rabbinic, medieval, and (early) modern Jewish texts and investigate practical measures to restore health after public and personal disasters. The focus on health distinguishes this volume from earlier works on Jewish medicine and makes it relevant for contemporary discussions on health maintenance and recuperation"--
Includes bibliographical references and index
Keywords: Health -- Religious aspects -- Judaism; Aufsatzsammlung